Estimating the need for diabetic retinopathy services in north India: evidence from a population-based survey in the catchment population of an eye care provider in central Uttar Pradesh - Andrew Bastawrous; Vaibhav Jain; Ian McCormick; Shalinder Sabherwal; Ishaana Sood; Atanu Majumdar; Shamanna B R; Mohd Javed; Sandeep Buttan; Simrat Chandi; Basitali Lakhani; Shreya Tyagi; et al. (BMJ Open)
Objective The aim of this study was to assess the prevalence of diabetic retinopathy (DR) and retina screening coverage among people with diabetes in the catchment area of a high-volume eye care organisation in north India.Design A population-based cross-sectional study using Rapid Assessment of Avoidable Blindness survey, including the DR module.Setting A customised rural district in the catchment of Dr Shroff’s Charity Eye Hospital in Uttar Pradesh in north India.Participants 4095 people of age 50 years and above were enrolled using a two-staged cluster sampling, 3867 (94.4%) participated; 2167 (52.9%) were women. 3803 of 4095 (92.9%) participants were assessed for diabetes. People with already diagnosed diabetes and anyone with a random blood glucose ≥200 mg/dL were offered dilated fundus examination.Primary and secondary outcomes Primary and secondary outcomes were the prevalence of DR and screening coverage for DR, respectively.Results The prevalence of diabetes was 7.0% (95% CI 5.9% to 8.0%). 50.2% of all people with diabetes were newly detected. The prevalence of any DR among people with diabetes who consented to dilated pupillary examination was 22.8% (51 of 224), (95% CI 18.2% to 27.3%). 5.8% (13/224) of people with diabetes were found to have sight-threatening DR and only 15.4% (2/13) had received treatment. 84.8% of people with previously diagnosed diabetes had never had their eyes tested for DR; this was significantly higher in women (90.2% vs 76.0%, respectively, p<0.001). 76% of people with previously diagnosed diabetes had poorly controlled diabetes; this was significantly higher for those on non-allopathic treatment (p<0.01). The odds of DR were higher with duration of diabetes >10 years and poor glycaemic control (OR of 1.8 and 1.6, respectively), but this was not found to be statistically significant.Conclusion The prevalence of DR in this predominantly rural setting was found to be higher than the national average. Coverage of retinal screening and treatment was found to be very low. Working with general health providers to increase detection of people with diabetes and leveraging vision centres to improve DR screening coverage is needed in this region.